Realignment and Party Revival. - Paulson, Arthur C. (Spring;Political Science., 1998)
Keywords: dept.psc; faculty_collection; sabbatical_report

Przemysl, Poland; a Study in Regard to Its East Europe/West Europe Frontier. - Best, Paul J. (1997)
Keywords: dept.psc; faculty_collection; sabbatical_report

Affirmative Action in Higher Education. - Rai, Kul B. (Spring;Political Science., 1996)
Keywords: dept.psc; faculty_collection; sabbatical_report

Center-Right Political Coalitions in American National Politics. - Weed, Clyde (1996)
Keywords: dept.psc; faculty_collection

Affirmative Action in Higher Education. - Critzer, John (1995)
Keywords: dept.psc; faculty_collection; sabbatical_report

Greek Civil War of 1946-1949. - Iatrides, John O. (1992)
Keywords: dept.psc; faculty_collection; sabbatical_report

Governing Through Turbulence: Leadership and Change in the Late 20th Century. - Walsh, David (1991)
Keywords: dept.psc; faculty_collection

America in the 21st Century: Challenges and Opportunities in Domestic Politics - Rai, Kul B.; Walsh, David F.; Best, Paul J. (Prentice Hall, 1998)
Keywords: 1989-; Political planning; Politics and government; United States; United States; dept.psc; faculty_collection

Carpatho-Slavic Studies. - Best, Paul J.; Carpatho-Slavic Studies Group (Carpatho-Slavic Studies Group, 1995)
Publication Title: Carpatho-Slavic studies.
Keywords: Carpatho-Rusyns; History; Periodicals; dept.psc; faculty_collection

Governing Through Turbulence: Leadership and Change in the Late Twentieth Century - Walsh, David F.; Best, Paul J.; Rai, Kul B. (Praeger, 1995)
Keywords: Case studies; Comparative government; Political leadership; dept.psc; faculty_collection

Political Alignment in the French National Assembly, 1789-1791 - Applewhite, Harriet Branson (Louisiana State University Press, 1993)
In this richly detailed study Harriet B. Applewhite analyzes the political alignment and loyalties of the deputies elected to the Estates General/National Assembly between 1789 and 1791. Her purpose is to understand how these men shaped the struggle that transformed France's constitutional structure and invented its modern political practices., To gauge the deputies' political alignments, Applewhite establishes categories based on their voting records, club memberships, signatures on protest lists, assessments by contemporary observers, and other evidence. She then arranges on a left-to-right scale all 1,318 of these individuals. For a selected group of deputies she uses published political pamphlets and biographical records not only to assess and compare their attitudes on issues concerning political legitimacy and political participation but also to establish and analyze connections between these attitudes and actual political behavior., Applewhite's investigation focuses on the origins of the deputies' understanding of French national unity, the nature and basis of the fierce partisan battles that raged in the National Assembly, and the changes in political institutions and practices that were handed down to postrevolutionary France. Contrary to the converging-elites theory popular among many students of the French Revolution, Applewhite finds that membership in one of the three estates of the Old Regime - the clergy, the aristocracy, and the commonalty - channeled the early careers of future deputies, their subsequent political opportunities, and their responses to the power struggles of the National Assembly., Applewhite defines two key legacies of the first National Assembly for the future of French legislative politics: first, a reluctance to compromise and an absence of trust that developed among participants at the outset and hardened throughout the twenty-eight months of the assembly; second, the development of a left, center, and right political culture within the National Assembly and a style of conflict that pulled both leaders and followers away from the center. This meticulously researched and carefully written work makes a significant and lasting contribution to the study of the French Revolution and points to new avenues of inquiry.–(Source of description unspecified.)
SCSU Faculty Scholar Award
Keywords: 1789-1799; 18th century; France; France; France. Assemblée nationale constituante (1789-1791); History; History; France. États généraux; History; Legislators; Politics and government; award_winner; dept.psc; faculty_collection

Women and Politics in the Age of the Democratic Revolution - Applewhite, Harriet Branson; Levy, Darline Gay (University of Michigan Press, 1990)
Keywords: 18th century; 18th century; Revolutions; 18th century; Women; Europe; History; Political activity; United States; Women; dept.psc; faculty_collection

The affirmative action debate - Critzer, JW (Ethnic and Racial Studies, 1999)
tex.unique-id: ISI:000081559400021
Keywords: dept.psc; ⛔ No DOI found

Book Review: Party ideologies in america, 1828–1996. by gerring john. new york: cambridge university press, 1998. 337p. 64.95. - Weed, Clyde P (American Political Science Review, 1999)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/053-253-900-453-573 tex.type: [object Object]
Keywords: book.review; dept.psc

Blacks and women in public higher education: Political and socioeconomic factors underlying diversity at the state level - Critzer, John W.; Rai, Kul B. (Women & Politics, 1998)
In this paper, we analyze the political and socioeconomic factors that may be associated with black and female employment in American public higher education. We develop representation ratios for black females, black males, white females, and white males who serve as full-time faculty members in public higher education institutions in the American states. Our analysis shows that region, in this case the South, provides the best indicator for black female and black male faculty employment in public higher education. The percentage of black state legislators is also associated with black faculty employment. For white women, we found that although they are well represented on faculties, their numbers do not reach their share of the population. None of the variables examined explained their employment as faculty members. Women as a group had a particularly weak presence in state legislatures and continue to have less political power than blacks and white males. We suggest a number of possible avenues for future research to clarify these findings.
_eprint: https://doi.org/10.1300/J014v19n01_02 tex.ids: ISI:000073528000002 tex.organization: Int Polit Sci Assoc tex.unique-id: ISI:000073528000002
Keywords: dept.psc; ⚠️ Invalid DOI

Racial and gender income inequality in the American states - Critzer, John W (Race and Society, 1998)
The purpose of this article is to uncover the political factors associated with greater income parity for black men, black women, and white women relative to white men in the American states. Variables are constructed for federal, state, and local government employment, state electoral competition, federal procurement, black state legislators, and women state legislators along with a number of socioeconomic factors. It is discovered that the political variables carry less weight than the socioeconomic ones. These findings raise questions about the future prospects for increased earnings parity for minorities and women as previous federal efforts to eliminate racial and gender discrimination appear to have been weakened and state political factors have little relationship with greater income equality.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/074-943-206-707-051 tex.type: [object Object]
Keywords: dept.psc

Book Review: Parties and politics in post-1989 poland . by hubert tworzecki. boulder, CO: westview press, 1996. 219p. 54.00. - Best, Paul J (American Political Science Review, 1997)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/169-906-379-339-236 tex.type: [object Object]
Keywords: book.review; dept.psc

Building a democratic order: Reshaping American liberalism in the 1930s and 1940s - Plotke,D - Weed, Clyde P (American Political Science Review, 1997)
0 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: dept.psc

Number and reason - the french revolution and the elections (french) - Gueniffey,P - Applewhite, HB (Journal of Modern History, 1995)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1995TP02700042
Keywords: dept.psc

Book Reviews - Critzer, John W. (The American Review of Public Administration, 1995)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1995RY11400008 tex.unique-id: [object Object]
Keywords: book.review; dept.psc

Poland's Journalists: Professionalism and Politics. By Jane Leftwich Curry. New York: Cambridge University Press, 1990. 302p. $54.50. - Best, Paul J. (American Political Science Review, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1991HD02200081 tex.unique-id: [object Object]
Keywords: dept.psc

Intervention and underdevelopment - greece during the cold-war - kofas,jv - Iatrides, JO (American Historical Review, 1991)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1991FK33500024
Keywords: dept.psc

Book Review: Sergei khrushchev. khrushchev on khrushchev: an inside account of the man and his era. edited and translated by william taubman. boston: little, brown and company, 1990. 423 pp.24.95. - Best, Paulj (Russian History-histoire Russe, 1990)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/017-251-197-152-167 tex.type: [object Object]
Keywords: book.review; dept.psc